Profile of PD-1 and PD-L1 mRNA Expression in Peripheral Blood of Nasopharyngeal Carcinoma - Muhammad Al Al Azhar; Siti Nadliroh; Karisma Prameswari; Handoko Handoko; Demak Lumban Tobing; Cita Herawati (Cell and BioPharmaceutical Institute, 2020)
Background: Programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1) expression is associated with prognostic and respond to immunotherapy with immune checkpoint inhibitor in several solid malignancies. However, the prognostic roles of PD-1 and PD-L1 expression in nasopharyngeal carcinoma (NPC) are less clear. This study aims to investigate PD-1 and PD-L1 mRNA expression levels in peripheral blood of Indonesian NPC patients and its association with clinicopathological features.Materials and Methods: This study used blood samples of 21 NPC patients and 10 healthy volunteers as controls. Real-time polymerase chain reaction (PCR) was used to measure mRNA expression of PD-1 and PD-L1.Results: PD-1 mRNA expression levels were significantly lower in NPC patients (∆CT mean: 9.65±2.04) compared to healthy individuals (∆CT mean: 8.04±1.51) (p=0.031). In contrast, PD-L1 mRNA expression levels were higher in NPC patients (∆CT mean: 6.96±1.32) compared to healthy individuals (∆CT mean: 7.11±0.55), but the difference was not statistically significant (p=0.554). The expression of PD-1 was associated with tumour-node-metastasis (TNM) stage (p=0.030) but not associated with age (p=1.000), sex (p=1.000), body mass index (p=0.350), tumor stage (p=0.338), nodal stage (p=0.579), metastasis stage (p=0.371), and Eastern Cooperative Oncology Group (ECOG) status (p=0.228). Meanwhile PD-L1 expression was not associated with all clinicophatological features.Conclusion: The PD-1 mRNA expression levels were significantly lower, while PD-L1 expression levels were higher in NPC patients compared to healthy controls. PD-1 expression was correlated with TNM stage.Keywords: nasopharyngeal carcinoma, immune checkpoint inhibitors, PD-1, PD-L1